Anatomy of Coping : Evidence from People Living through the Crises of 2008–11 - Heltberg, Rasmus; Hossain, Naomi; Reva, Anna; Turk, Carolyn (2012)
This paper surveys qualitative crisis monitoring data from sites in 17 developing and transition countries to describe crisis impacts and analyze the responses and sources of support used by people to cope. These crises included shocks to export sectors as a result of the global financial crisis, as well as food and fuel price volatility, in the period from 2008 to early 2011. Respondents reported the crisis had resulted in significant hardships in the form of foregone meals, education, and health care, food insecurity, asset losses, stress, and worsening crime and community cohesion. Although the export-oriented formal sector was most exposed to the global economic downturn, the crises impacts were more damaging for informal sector workers, and some of the adverse impacts will be long-lasting and possibly irreversible. There were important gender and age differences in the distribution of impacts and coping responses, some of which diverged from what has been seen in previous crisis coping responses. The more common sources of assistance were family, friends, and community-based and religious organizations; formal social protection and finance were not widely cited as sources of support in most study countries. However, as the crisis deepened, the traditional informal safety nets of the poor became depleted because of the large and long-lasting shocks that ensued, pointing to the need for better formal social protection systems for coping with future shocks.